Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T15:45:26+01:00
A)2-x=5-2x
-x+2x=5-2
x=3
b) 69-x=x+96
-x-x=96-69
-2x=27 |/ (-2)
x=-13,5
c)3x-1=5x
3x-5x=1
-2x=1 |/(-2)
x=-½
d)y-3=9-y
y+y=9+3
2y=12 |/2
y=6
e)½z+6=z-1
½z-z=-1-6
-½z=-7 | *(-2)
z=14
1 5 1
2010-03-11T15:49:22+01:00
A)2-x=5-2x
x+2x=5-2
3x=3//:3
x=1
b) 69-x=x+96
-x-x=96-69
-2x=-27
x=13,5
c)3x-1=5x
3x-5x=1
-2x=1
x= -0,5
d)y-3=9-y
y+y=9+3
2y=12
y=6
e)½z+6=z-1
½z-z=-1-6
-½z=-7
z=14
1 5 1
2010-03-11T15:54:33+01:00
A) 2-x = 5-2x
-x+2x=5-2
x=3

b) 69-x=x+96
-x-x=96-69
-2x=27 /-2
x=-13,5

c) 3x-1=5x
3x-5x=1
-2x=1/-2
x=-1/2

d) y-3=9-y
y+y=9+3
2y=12/2
y=6

e) 1/2z+6=z-1
1/2z-z=-1-6
-1/2z=-7/-1/2
z=3,5
1 5 1